Establishment of a Personalized External Aortic Root (PEARS) Program: A Single Center Experience. (9th April 2021) - O' Sullivan, Katie E.; Fleville, Samara; Ball, Peter; Graham, Alastair N.J.
Abstract : Objective : Personalized external aortic root support (PEARS) is a novel approach in the management of aortic root aneurysms in those with connective tissue disorders. The objective of this study is to review the initial experience and outcomes from a single center. Methods : A PEARS program was established with a proctor present for the first three cases. A retrospective review of all patients undergoing PEARS from 2016 to present was undertaken. Results : We have treated 14 patients to date, 12 isolated PEARS and 2 with concomitant procedures. Of the isolated PEARS patients, mean duration of procedure was 196 ± 31 minutes. Median hospital stay was 7 days (range 4-118). There were no mortalities. Complications included atrial fibrillation (n=2) and transient ST elevation (n=4), late onset pericarditis (n=1). One patient developed intra operative ischemia following mitral repair and PEARS requiring emergency CABG and resulting in a prolonged stay. One patient with Loeys Dietz developed a right coronary artery dissection post operatively which was managed with re-operation, vessel ligation and CABG. Two patients had moderate aortic incompetence which was significantly improved following PEARS. Mean follow up is 1.2 ± 1 years and all patients are well with no acute aortic events. Conclusions : We successfully established a PEARS program. Coronary complications post PEARS can be life threatening. We recommend requesting pre discharge CT aorta for all patients. Longer term follow of aortic dimensions is required to determine efficacy. Further investigation of the role of PEARS in treating patients with aortic regurgitation is required to establish the role of PEARS in this context.